A nation-wide study on the prevalence of non-collision injuries occurring during use of public buses. (June 2019) - ,; Bahouth, H.; Becker, A.; Jeroukhimov, I.; Karawani, I.; Kessel, B.; Klein, Y.; Lin, G.; Merin, O.; Bala, M.; Mnouskin, Y.; Rivkind, A.; et al.
Abstract: Introduction: Bus public transportation is preferred for its perceived safety. Data from several countries, however, alarm of non-collision injuries associated with bus use. The aim of the current study was to estimate the prevalence of non-collision bus injuries, and compare and identify population group at high risk for severe injuries, to serve as a basis for policy makers. Methods: A retrospective analysis of the Israeli National Trauma Registry cohort for the years 2015–2017 was carried out. Database consists of 20 hospitals nationwide. Casualties hospitalized following a non-collision injury on a bus were identified. Demographic, injury characteristics, and hospital resources utilization were compared according to the place of injury; inside the bus or during boarding or alighting. Results: During follow up, 704 hospitalized non-collision related bus casualties were recorded. Most of the casualties (75%) fell inside the bus and 25% during boarding or alighting. The majority (67%) of hospitalized patients were 60 years old or above, mostly injured while boarding or alighting the bus, and 72% were women. Frequent injured body regions were lower extremities, head and torso. Passengers injured inside bus sustained more chest injuries, but less lower extremities injuries, compared to those boarding or alighting the bus. More hospital resources were required to treat passengers injured while boarding or alighting the bus. Conclusions: This systematic registry-based analysis of non-collision bus injuries confirms the greater risk of being injured while using bus transportation among women and older passengers. Primary attention for prevention policies should be given to injuries occurring during boarding or alighting of the bus. Additional policy recommendations are discussed. Highlights: Travel by bus is thought to be safe, yet non-systematic data suggests otherwise. Women and older passengers (>60 years) are disproportionally hospitalized following non-collision injuries in buses. The greater risk of injury is posed to passengers boarding and alighting the bus.